Urszula Kraśnicka, Krzysztof Filipow (red.) "Bitwa Niemeńska" - Trzeciakowska, Sylwia (2000)
Recenzja książki.
Nazwa aut. recenzji pod tekstem.
Keywords: Książki -- recenzje -- 1970-2000.; Niemen, Bitwa (1920) -- konferencje; Wojna polsko-bolszewicka (1919-1920) -- konferencje